Study on Control Technology for Working Faces Passing through Long-Span Abandoned Roadways. (28th November 2020) - Liu, Zhenghe; Ye, Hailong; Yang, Lusheng; Wang, Shaohua; Zhang, Junwen; Zhang, Baisheng; Li, Zhiqiang
Abstract : The width of an abandoned roadway has a great influence on the roof stability of the working face. According to the coal seam conditions of the 30106 working face in the Sanyuan Shiku mine, the advance of a working face through an abandoned roadway was studied by using theoretical analysis, similar material simulation, numerical simulation, and field testing to determine the law of stope roof fracture migration, the stress distribution characteristics, and the variation in support resistance. Several conclusions are drawn: (1) The roof of the overlying strata is fractured at the edge of the abandoned roadway in front of the coal pillar and rotates downward due to the run-through of the plastic zone between the working face and abandoned roadway. (2) The hydraulic support working resistance gradually increases with decreasing coal pillar width between the working face and abandoned roadway, and the working resistance of the support tends to peak when the plastic zone extends to the coal, resulting in 3 4 times the normal recovery. Leakage occurred in front of the support in the caving zone. (3) The analysis of the relationship between the support and surrounding rock with the mechanical model for calculating the support load allows the derivation of the support working resistance formula for a working face passing through an abandoned roadway. (4) When the working face is excavated to expose the abandoned roadway, the shrinkage of the front column of the hydraulic support is significantly greater than that of the back column, and the stability is greatly reduced. This problem can be effectively solved when the uniaxial compressive strength of the backfill ≥2 MPa. (5) The engineering practice showed that the danger of leakage and roof fracture impact load was eliminated with the mining pressure reduction after reinforcement measures were taken in the abandoned roadway. The working face passed the abandoned roadway safely, providing the theoretical basis and guidance for coal remining under similar conditions.